2010
DOI: 10.1029/2009jg001082
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of increasing dissolved organic carbon levels on pH in lakes recovering from acidification

Abstract: [1] In this study, we examine the impact of increasing concentrations of dissolved organic carbon (DOC) on the recovery from acidification for 66 lakes in Southern Sweden. The lakes are small, weakly buffered, and have all been affected by acidifying deposition. A majority of the lakes (∼75%) showed an increase in DOC concentrations between 1990 and 2008. The method used in this study was to model pH in 2008 from DOC, acid neutralizing capacity, pCO 2 (partial carbon dioxide pressure), and Al speciation, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…), which suppresses recovery of pH and alkalinity (Erlandsson et al . ). This may explain the long‐term stability of pH and alkalinity and decreasing water clarity observed in hemiboreal lakes.…”
Section: Discussionmentioning
confidence: 97%
“…), which suppresses recovery of pH and alkalinity (Erlandsson et al . ). This may explain the long‐term stability of pH and alkalinity and decreasing water clarity observed in hemiboreal lakes.…”
Section: Discussionmentioning
confidence: 97%
“…These models have been extensively validated against measured carbon fluxes at particular sites around the world (Krinner et al, 2005;Sitch et al, 2003); they also realistically simulate observed historical change in leaf area index (LAI) and transient responses of carbon fluxes to climate variability (Lutch et al, 2002;Ciais et al, 2005;Piao et al, 2006Piao et al, , 2008. Tao and Zhang (2010) have also validated LPJ derived NPP and carbon storage against observation in China. Terrestrial NEP fluxes from ORCHIDEE have also been successfully validated against measured carbon fluxes at particular sites in China (Tan et al, 2009;Peng et al, in prepare).…”
Section: Ecosystem Modelsmentioning
confidence: 99%
“…The meteorological data (air temperature, precipitation, wet day frequency, diurnal temperature range, cloud cover, relative humidity of the air, and wind speed) with spatial resolution of 0.5°for 1901-2002 were supplied by the Climatic Research Unit (CRU), School of Environmental Sciences, University of East Anglia, U.K. (Mitchell and Jones, 2005), while annual global atmospheric CO 2 concentrations for the period 1901-2002 were based on data from ice-core records and atmospheric observations (Keeling and Whorf, 2005). Both ORCHIDEE and SDGVM used prescribed actual vegetation (Loveland et al, 2000), while LPJ calculated its own vegetation distribution (Sitch et al, 2003;Tao and Zhang, 2010). Soil texture distribution information was derived from the Zobler (1986) soil texture map.…”
Section: Model Runsmentioning
confidence: 99%
“…However, over-reliance on simple models and purely statistical criteria may lead to overly simplistic views of the environment. If nothing else, it can be argued that more than 30 years of research into surface water DOC, and its links to acidification, acidity, climate and hydrology (Krug and Frink 1983;Laudon et al 1999;Erlandsson et al 2008Erlandsson et al , 2010Lepistö et al 2008;Clark et al 2010;Haaland et al 2010;Haei et al 2010;Löfgren et al 2010b;Löfgren and Zetterberg 2011), has shown that numerous factors influence or covary with surface water DOC. So, we must conclude that, on the basis of our current understanding, reality is over-determined but that models can be a useful tool for environmental hypothesis testing and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in [DOC] also affect the timing and magnitude of thermal stratification in lakes, with consequent effects on ecological processes and mercury dynamics (Forsius et al 2010). In addition, increasing [DOC] has been shown to affect pH recovery in many surface waters (Erlandsson et al 2010).…”
Section: Introductionmentioning
confidence: 99%